Oktawa w epice historycznej wieków dawnych – wybrane problemy (na przykładzie Pamiętnego uprowadzenia wojska z cieśni bukowińskiej… Stanisława Wincentego Jabłonowskiego) - Piątek, Marcin (Śląskie Studia Polonistyczne, 2019)
The article is divided into two parts. The first one describes a career that ottava rima had in seventeenth-century heroic narrative poems. What the author references are the most valid opinions by scholars of the Polish verse pertaining to ottava rima, in addition to the opinions by the poets who struggled to write in this challenging stanza form. Part two of the article analyses selected stanzas (ottavas) from the narrative poem Pamiętne uprowadzenie wojska z cieśni bukowińskiej… (1745) by Stanisław Wincenty Jabłonowski. Aside from versological questions, also the most important problems are indicated that relate to editing and punctuation of the Jabłonowski’s ottava rima.